Unsur Melawan Hukum Sebagai Suatu Sarana Dalam Delik Pasal 2 Ayat (1) UU Nomor 31 Tahun 1999 Tentang Tipikor - Muhammad Ridwan Lubis; Halimatul Maryani; Cut Nurita (Universitas Merdeka Madiun, 2019)
In all of the regulations, unless the Act No. 24 / Prp / 1960, the definition of 'unlawful' means has a broad meaning, namely in terms of formal (formele wederrechtelijkheid) and in terms of material (materiele wederrechtelijkheid), without distinguishing function is positive or negative function. This can be seen in the general explanation of these various regulations, as well as according to general explanations PTPK the existing laws in addition to an explanation related to Article 2 paragraph (1), as disampaikansebelumnya.Dalam its development in the future, the interpretation of